Wild bats hunt insects faster under lit conditions by integrating acoustic and visual information - Laura Stidsholt; Mara Zebele; Carolin Scholz; Christian C. Voigt (Proceedings of the National Academy of Sciences, 2025)
Animals can improve their decision-making abilities by integrating information from multiple senses, which is especially beneficial when living in fluctuating environments. However, understanding how wild predators may use multimodal sensing when hunting prey in split-second interactions remains largely unexplored. As nocturnal hunters, bats rely on echolocation to navigate and to locate evasive prey, yet they have retained functional vision, despite the associated costs. We therefore hypothesized that bats use vision to enhance sensory redundancy when commuting and tracking small insects. To test this, we equipped 21 wild common noctule bats ( Nyctalus noctula ) with high-resolution light, sound, and motion sensor loggers and measured their echolocation and movements while commuting and foraging in both dark and lit environments. When commuting, the bats maintained consistent echolocation sampling across light levels. However, when tracking prey in illuminated environments, the bats emitted calls with half the rate and with 7 dB higher call levels compared to in dark conditions, but at much faster approach speeds (from 5.2 in darkness to 7.9 m/s in lit conditions). This suggests that, in illuminated environments, hunting bats integrate acoustic and visual information, resulting in more efficient approaches to prey. Our findings demonstrate how a wild sensory specialist predator uses multimodal sensing to hunt efficiently in highly dynamic resource landscapes.